Patterns and Determinants of Organized Dairy Industry growth: A Panel Study - rathore, Shiv raj singh (Indian Journal of Dairy Science, 2018)
Milk processing in India is around 35 per cent, of which the organized dairy industry accounts for 13 per cent of the milk produced, the remaining 22 per cent is processed in the unorganized sector. The locational pattern of organised dairy factories in India depicted a skewed distribution across the states and regions during the study period. Andhra Pradesh, Tamil Nadu, Maharashtra and Gujarat were the leading states in organised dairy manufacturing which together accounted for 70 per cent of the total factories in India. The region-wise analysis showed that the maximum number of dairy factories were located in the Southern region followed by Western, Central, Northern and Eastern regions, respectively. In India, growth rate of organised dairy factories was around 8 per cent over the study period. However, at regional and state level the growth rates were not uniform. Across different regions, growth rates of organised dairy factories were positive except for Eastern region. As per the results of two-way fixed effect model, productivity of milch animals negatively influenced the throughput of milk used in organised dairy industry. On the other hand female bovine population positively influenced the throughput of milk in the organised dairy industry. It is important to note that the expenditure on milk and milk products negatively influenced the throughput of milk in the organised dairy industry. Buffalo-cattle ratio significantly positive influenced the throughput of milk. Similarly, at regional level, various factors behaved differently (sign) and their magnitude differed substantially. As expected, female bovine population positively influenced the throughput of milk across the Central, Northern and Southern regions. Similarly, buffalo-cattle ratio was important factor in the Southern region of India. However, in Northern and Western regions productivity of milch animals has negatively influenced the throughput of milk used in the organised dairy industry.